The interaction effects of smoking and polycyclic aromatic hydrocarbons exposure on the prevalence of metabolic syndrome in coke oven workers. (May 2020) - Zhang, Bin; Pan, Baolong; Zhao, Xinyu; Fu, Ye; Li, Xuejing; Yang, Aimin; Li, Qiang; Dong, Jun; Nie, Jisheng; Yang, Jin
Abstract: Introduction: Metabolic syndrome (MetS) is a cluster of interrelated risk factors, which increase the risk of cardiovascular disease (CVD) and cancer. The prevalence of MetS might be affected by environmental pollution and individual's poor lifestyles. Methods: In this cross-sectional study, we aimed to evaluate the interactions effect of PAHs exposure and poor lifestyles on MetS among coke oven workers. We measured the concentrations of 11 urinary PAH metabolites among 682 coke oven workers by HPLC-MS. China adult blood lipid abnormality prevention guide (2016) was employed for diagnosing MetS. An interaction effect was tested in the modified Poisson regression models. Results: The results showed that the urinary level of 1-NAP ( P for trend = 0.043) and 2-FLU ( P for trend = 0.037) had significant dose-response relationships with increased PR of MetS. For 1-NAP, statistically significant positive association was with low HDL among individuals ( P for trend = 0.003). Besides, smoking was associated with a significantly increased risk of prevalence ratio of MetS (PR = 1.07; 95% CI 1.00–1.13), high triglycerides (PR = 1.13; 95% CI 1.05–1.20) and low HDL (PR = 1.07; 95% CI 1.01–1.14). Smokers who with high levels of 1-NAP and 2-FLU had higher prevalence ratio of MetS compared with non-smokers who with low levels of 1-NAP [PR (95% CI): 1.17 (1.06–1.29); P for trend = 0.002] and 2-FLU [PR (95% CI): 1.17 (1.06–1.29); P for trend = 0.004]. Conclusions: Our findings suggested PAHs exposure increased the prevalence ratio of MetS and this effect can be modified by smoking status. Graphical abstract: Image 1 Highlights: Relationship of PAH exposure and MetS was analysed by modified Poisson regression. PAHs exposure can increase the prevalence ratio of MetS in coke oven workers. Smoking modifies the prevalence ratio of MetS induced by PAHs exposure.